Anti-corrosion epoxy composite coating and preparation method thereof

By using porous microspheres to load polythiophene and modified hexagonal boron nitride in epoxy coating, and improving dispersion through nanoparticle functionalization, the insufficient anticorrosion performance and poor polythiophene compatibility of hexagonal boron nitride coating are solved. The problem of this achieves better corrosion resistance.

CN119286347APending Publication Date: 2025-01-10NINGBO KEXIN CORROSION CONTROL ENG
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411387857.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-07
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

During the film formation process of hexagonal boron nitride type epoxy coating, there is loss of volatile substances and particles prone to agglomeration, resulting in insufficient barrier properties on corrosive media, and poor compatibility with polythiophene and epoxy coating, making it difficult to disperse effectively, affecting Anti-corrosion performance.

Method used

Porous microspheres loaded polythiophene and modified hexagonal boron nitride are used to function hexagonal boron nitride through electrochemical protection, passivation and oxygen absorption reaction mechanisms, combined with nanoparticles to improve anticorrosion performance, and polydopamine and iron ions are used. Compound improves dispersion.

Benefits of technology

It significantly improves the corrosion resistance of the hexagonal boron nitride type epoxy coating, extends the corrosion time, enhances the corrosion resistance of the coating, and avoids direct contact and loss of polythiophene and hexagonal boron nitride.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of coating materials, in particular to an anti-corrosion epoxy composite coating and a preparation method thereof. The anti-corrosion epoxy composite coating is prepared from the following raw materials in parts by mass: 40 to 60 parts of epoxy resin, 10 to 20 parts of alkoxy silane, 4 to 6 parts of pigment, 1 to 4 parts of auxiliaries, 2 to 6 parts of solvents, 14 to 18 parts of hexagonal boron nitride type preservatives and 10 to 30 parts of curing agents, and the hexagonal boron nitride type preservatives contain hexagonal boron nitride and polythiophene. According to the anti-corrosion epoxy composite coating, the defect that hexagonal boron nitride particles are prone to agglomeration can be overcome, and the anti-corrosion epoxy composite coating has more excellent anti-corrosion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coating materials, and more specifically, to an anti-corrosion epoxy composite coating and a preparation method thereof. Background Art

[0002] Carbon steel is the most widely used metal substrate in the world, but it is easily corroded by moisture and oxygen under atmospheric conditions, which seriously restricts its application and development. Organic coatings have excellent barrier properties to protect carbon steel from corrosion. Among them, epoxy coatings have received special attention due to their excellent bonding properties.

[0003] However, since volatile substances will inevitably be lost during the film-forming process of epoxy resin, shrinkage and defects will occur inside the epoxy coating, which greatly weakens its barrier performance against corrosive media. When two-dimensional materials with nano-barrier effects are added to the coating as nanomaterials, they can act synergistically with the organic coating to further enhance the anti-corrosion protection performance of the organic coating through physical barrier and cathodic protection.

[0004] Hexagonal boron nitride is a new type of two-dimensional material. Due to its lamellar structure and wide bandgap semiconductor properties, when hexagonal boron nitride is used as a polymer filler, it will obtain extremely excellent corrosion resistance. However, due to the different electronegativity of the B atoms and N atoms in hexagonal boron nitride, the ionic bond interaction between the two causes the hexagonal boron nitride particles to easily agglomerate, thereby affecting its anti-corrosion performance. Summary of the invention

[0005] In order to improve the defect that the anti-corrosion performance of hexagonal boron nitride epoxy coating is still insufficient, the present application provides an anti-corrosion epoxy composite coating and a preparation method thereof.

[0006] In the first aspect, the present application provides an anti-corrosion epoxy composite coating, which adopts the following technical solution: An anti-corrosion epoxy composite coating comprises the following raw materials in parts by weight: 40-60 parts of epoxy resin, 10-20 parts of alkoxysilane, 4-6 parts of pigment, 1-4 parts of auxiliary agent, 2-6 parts of solvent, 14-18 parts of hexagonal boron nitride type preservative and 10-30 parts of curing agent, wherein the hexagonal boron nitride type preservative contains hexagonal boron nitride and polythiophene.

[0007] Polythiophene is a corrosion inhibitor that can slow down or even prevent metal corrosion. Its anti-corrosion mechanism includes electrochemical protection, passivation and oxygen absorption reaction. Among them, electrochemical protection means that when the corrosive medium contacts polythiophene, polythiophene can prevent the flow of current, thereby reducing the electrochemical corrosion rate of the metal. Passivation means that polythiophene can form an alloy layer with the metal surface, and the alloy layer can change the chemical state of the metal surface to form a passivation film, thereby improving the corrosion resistance of the metal. Oxygen absorption reaction means that polythiophene can participate in the adsorption and release process of oxygen, and affect the kinetics of the corrosion reaction by adjusting the concentration of oxygen on the metal surface.

[0008] Therefore, when polythiophene and hexagonal boron nitride are used at the same time, polythiophene and hexagonal boron nitride will simultaneously provide corrosion protection in multiple aspects such as physical barrier, electrochemical protection, passivation and oxygen absorption reaction, thereby further improving the anti-corrosion performance of hexagonal boron nitride epoxy coating.

[0009] Preferably, the hexagonal boron nitride preservative is composed of modified hexagonal boron nitride, porous microspheres and polythiophene.

[0010] Although polythiophene can exert a synergistic anti-corrosion effect with hexagonal boron nitride, similar to hexagonal boron nitride, polythiophene has relatively poor compatibility with the epoxy coating matrix, that is, polythiophene is difficult to disperse in the epoxy coating, which makes it easy for polythiophene to accumulate or even flow away, resulting in poor anti-corrosion performance of the epoxy coating.

[0011] When porous microspheres, polythiophene and hexagonal boron nitride are used together, polythiophene and hexagonal boron nitride can be loaded in the porous microspheres, and the porous microspheres have excellent compatibility with the epoxy coating. The porous microspheres can also effectively prevent polythiophene and hexagonal boron nitride from direct contact with the epoxy matrix. Then, the polythiophene and hexagonal boron nitride are slowly released through the characteristics of the porous microspheres themselves, thereby significantly improving the anti-corrosion performance of the hexagonal boron nitride epoxy coating.

[0012] Preferably, the mass ratio of the modified hexagonal boron nitride, porous microspheres and polythiophene is (8-10):1:(3-4).

[0013] When the modified hexagonal boron nitride, porous microspheres and polythiophene are in the above mass ratio, the prepared hexagonal boron nitride epoxy coating will have better anti-corrosion performance.

[0014] Preferably, the modified hexagonal boron nitride is dopamine-modified hexagonal boron nitride-nano ferrosoferric oxide.

[0015] Although porous microspheres can load polythiophene and hexagonal boron nitride, compared with liquid polythiophene, the two-dimensional sheet shape of hexagonal boron nitride itself is more difficult to load on porous microspheres.

[0016] Functionalizing hexagonal boron nitride with nanoparticles can effectively increase the dispersibility of hexagonal boron nitride and maintain its structural integrity, reducing the surface defects of hexagonal boron nitride. Dopamine can effectively improve interfacial adhesion, forming a polydopamine layer on the substrate surface, and can also be compounded with trivalent iron ions or divalent iron ions through catechol to load nano-ferroferric oxide on hexagonal boron nitride, thereby effectively improving the dispersibility of hexagonal boron nitride in epoxy coatings and indirectly improving the anti-corrosion performance of hexagonal boron nitride epoxy coatings.

[0017] Preferably, the modified hexagonal boron nitride comprises the following raw materials in parts by mass: 200-300 parts of Tris-HCl buffer, 0.5-1.0 parts of dopamine hydrochloride, 1-3 parts of hexagonal boron nitride, 2-5 parts of γ-aminopropyltriethoxysilane, 0.1-0.3 parts of nano-ferrosoferric oxide and 100-160 parts of N,N-dimethylformamide.

[0018] Preferably, the preparation method of the modified hexagonal boron nitride comprises the following steps: 1. Preparation of polydopamine modified hexagonal boron nitride First, dopamine hydrochloride is slowly added into Tris-HCl buffer and stirred continuously, then hexagonal boron nitride is quickly added and ultrasonically treated for 2-4 hours, and then balanced at 50-70°C for 12-36 hours, centrifuged and filtered to wash until the filtrate is colorless, and finally solid-liquid separation is performed, and the solid product is vacuum dried to obtain polydopamine-modified hexagonal boron nitride; Preparation of modified nano-iron tetroxide Add nano-ferroferric oxide and γ-aminopropyltriethoxysilane to anhydrous ethanol 20 times the mass of the raw material, then continue stirring for 20-40 minutes, ultrasonic treatment for 3-4 hours, then quickly add deionized water 2 times the mass of the raw material, stir at 70-90°C for 3-5 hours, centrifuge and wash, and vacuum dry to obtain the modified Nano-iron tetroxide; Preparation of modified hexagonal boron nitride The polydopamine-modified hexagonal boron nitride is mixed with N,N-dimethylformamide and ultrasonically treated for 1-2 hours. After forming a suspension, modified ferrosoferric oxide is added, and ultrasonic treatment is performed for 1-2 hours. Thereafter, the mixture is stirred at 100-110° C. for 5-7 hours, and finally, the mixture is centrifugally filtered, washed, and vacuum dried to obtain the modified hexagonal boron nitride.

[0019] Preferably, the porous microspheres are prepared by mixing trimethylolpropane triacrylate and toluene in a mass ratio of 1:(1-3), then adding 1wt% of the total mass of 2-hydroxy-2-methyl-1-phenyl-1-propanone, and preparing an oil phase under ultrasonic action; The oil phase is mixed with a 1wt% polyvinyl alcohol aqueous solution in a mass ratio of 1:(4-6), and then dispersed and emulsified. The emulsion is then subjected to UV curing treatment. The UV curing treatment conditions are: wavelength 365nm, power 120W, light source 25cm away from the emulsion, irradiation 5min, UV light initiates the self-polymerization of the monomer trimethylolpropane triacrylate to form microspheres, which are then washed and dried to obtain porous microspheres.

[0020] Preferably, the preparation method of the hexagonal boron nitride preservative is: First, the modified hexagonal boron nitride, polythiophene and ethanol are mixed to obtain a load solution, and then the porous microspheres are added to a three-necked flask equipped with a separatory funnel and a vacuum valve, the load solution is added to the separatory funnel, and then the air in the three-necked flask is removed through the vacuum valve, and the load solution is transferred to the three-necked flask through the separatory funnel, mixed and stirred for 4-6 hours under a vacuum environment, and finally filtered, washed and dried to obtain a hexagonal boron nitride preservative.

[0021] In a second aspect, the present application provides a method for preparing an anti-corrosion epoxy composite coating, which adopts the following technical solution: A method for preparing an anti-corrosion epoxy composite coating comprises the following steps: S1. First, epoxy resin and alkoxysilane are mixed, and then continuously stirred at 60-80° C. to obtain an epoxy matrix; S2, adding pigment, additive, solvent and hexagonal boron nitride preservative to the epoxy matrix in sequence, and then mixing and stirring for 10-20 minutes to obtain component A; S3. Mix the curing agent as component B with component A, and then apply the coating to obtain the anti-corrosion epoxy composite coating.

[0022] In summary, this application has the following beneficial effects: 1. Polythiophene is a corrosion inhibitor that can slow down or even prevent metal corrosion. Its anti-corrosion mechanism includes electrochemical protection, passivation and oxygen absorption reaction. When polythiophene and hexagonal boron nitride are used at the same time, polythiophene and hexagonal boron nitride will simultaneously provide anti-corrosion protection in multiple aspects such as physical barrier, electrochemical protection, passivation and oxygen absorption reaction, thereby further improving the anti-corrosion performance of hexagonal boron nitride epoxy coating.

[0023] 2. Polythiophene is difficult to disperse in epoxy coatings, which makes it easy for polythiophene to accumulate or even flow away, resulting in poor corrosion resistance of epoxy coatings. When porous microspheres, polythiophene and hexagonal boron nitride are used in combination, polythiophene and hexagonal boron nitride can be loaded in the porous microspheres, and the porous microspheres have excellent compatibility with epoxy coatings. In addition, the porous microspheres can effectively prevent polythiophene and hexagonal boron nitride from direct contact with the epoxy matrix. Then, the polythiophene and hexagonal boron nitride are slowly released through the characteristics of the porous microspheres themselves, thereby significantly improving the corrosion resistance of the hexagonal boron nitride epoxy coating.

[0024] 3. The two-dimensional flaky form of hexagonal boron nitride itself is more difficult to load on porous microspheres, but the functionalization of hexagonal boron nitride with nanoparticles can effectively increase the dispersibility of hexagonal boron nitride and maintain its structural integrity, reducing the surface defects of hexagonal boron nitride. Specifically, dopamine can be compounded with trivalent iron ions or divalent iron ions through catechol, so as to load nano-ferrosoferric oxide on hexagonal boron nitride, thereby effectively improving the dispersibility of hexagonal boron nitride in epoxy coatings and indirectly improving the anti-corrosion performance of hexagonal boron nitride epoxy coatings. DETAILED DESCRIPTION

[0025] The present application is further described in detail below in conjunction with Examples 1-7 and Comparative Example 1.

[0026] raw material Epoxy resin E-20; Alkoxysilane methyl trimethoxysilane CAS: 1185-55-3; Pigment titanium dioxide CAS: 1317-80-2; Auxiliary leveling agent BYK302; Solvent ethyl acetate CAS: 141-78-6; Curing agent T31 CAS: 98-67-9; Hexagonal boron nitride CAS: 10043-11-5; Polythiophene CAS: 155090-83-8; Tris-HCl buffer 0.01 mol / L; Dopamine hydrochloride CAS: 62-31-7; γ-aminopropyl triethoxysilane CAS: 919-30-2; Nano-iron tetroxide 20nm CAS: 1317-61-9; N,N-dimethylformamide CAS: 68-12-2; trimethylolpropane triacrylate CAS: 15625-89-5; toluene CAS: 108-88-3; 2-hydroxy-2-methyl-1-phenyl-1-propanone CAS: 7473-98-5; polyvinyl alcohol CAS: 9002-89-5; ethanol CAS: 64-17-5.

[0027] An anti-corrosion epoxy composite coating includes the following raw materials: 50kg epoxy resin E-20, 15kg alkoxysilane-methyltrimethoxysilane, 5g pigment-titanium dioxide, 2.5g auxiliary agent-leveling agent BYK302, 4kg solvent-ethyl acetate, 16kg hexagonal boron nitride preservative and 20kg curing agent T31.

[0028] The method for preparing the anti-corrosion epoxy composite coating comprises the following steps: S1. First, epoxy resin and alkoxysilane are mixed, and then continuously stirred at a temperature of 70° C. to obtain an epoxy matrix; S2, adding pigment, additive, solvent and hexagonal boron nitride preservative to the epoxy matrix in sequence, followed by mixing and stirring for 15 minutes to obtain component A; S3. Mix the curing agent as component B with component A, and then apply the coating to obtain the anti-corrosion epoxy composite coating.

[0029] Among them, the hexagonal boron nitride type preservative is composed of modified hexagonal boron nitride, porous microspheres and polythiophene, and the mass ratio of modified hexagonal boron nitride, porous microspheres and polythiophene is 9:1:3.5; The preparation method of hexagonal boron nitride type preservative is: First, the modified hexagonal boron nitride, polythiophene and twice the volume of ethanol are mixed to obtain a load solution. Then, the porous microspheres are added to a three-necked flask equipped with a separatory funnel and a vacuum valve. The load solution is added to the separatory funnel, and then the air in the three-necked flask is removed through the vacuum valve. The load solution is transferred to the three-necked flask through the separatory funnel, mixed and stirred for 5 hours under a vacuum environment, and finally filtered, washed and dried to obtain a hexagonal boron nitride preservative.

[0030] The modified hexagonal boron nitride is dopamine-modified hexagonal boron nitride-nano-ferroferric oxide; The modified hexagonal boron nitride comprises the following raw materials: 250kg Tris-HCl buffer, 0.8kg dopamine hydrochloride, 2kg hexagonal boron nitride, 3.5kg gamma-aminopropyltriethoxysilane, 0.2kg nano-ferrosilicate and 130kg N,N-dimethylformamide.

[0031] The preparation method of modified hexagonal boron nitride comprises the following steps: 1. Preparation of polydopamine modified hexagonal boron nitride First, dopamine hydrochloride was slowly added into Tris-HCl buffer and stirred continuously, then hexagonal boron nitride was quickly added and ultrasonically treated for 3 hours, and then balanced at 60°C for 24 hours, centrifuged and filtered until the filtrate was colorless, and finally solid-liquid separation was performed, and the solid product was vacuum dried to obtain polydopamine-modified hexagonal boron nitride; 2. Preparation of modified nano-iron tetroxide Add nano-ferroferric oxide and γ-aminopropyltriethoxysilane to anhydrous ethanol with a mass 20 times that of the raw material, then continue stirring for 30 minutes, ultrasonically treat for 4 hours, then quickly add deionized water with a mass 2 times that of the raw material, stir at 80°C for 4 hours, centrifuge and wash, and vacuum dry to obtain modified nano-ferroferric oxide; 3. Preparation of modified hexagonal boron nitride The polydopamine-modified hexagonal boron nitride was mixed with N,N-dimethylformamide and ultrasonically treated for 2 hours. After forming a suspension, modified ferrosoferric oxide was added, and ultrasonic treatment was performed for another 2 hours. Thereafter, the mixture was stirred at 105°C for 6 hours, and finally centrifugally filtered, washed, and vacuum dried to obtain the modified hexagonal boron nitride.

[0032] The porous microspheres are prepared by mixing trimethylolpropane triacrylate and toluene in a mass ratio of 1:2, then adding 1wt% of the total mass of 2-hydroxy-2-methyl-1-phenyl-1-propanone, and preparing an oil phase under ultrasonic action; The oil phase was mixed with 1wt% polyvinyl alcohol aqueous solution in a mass ratio of 1:5, and then dispersed and emulsified. The emulsion was then subjected to UV curing treatment. The UV curing treatment conditions were: wavelength 365nm, power 120W, light source 25cm away from the emulsion, irradiation 5min, UV light initiated monomer trimethylolpropane triacrylate to self-polymerize to form microspheres, which were then washed and dried to obtain porous microspheres.

[0033] The difference from Example 1 is that the addition amounts of the components of the anti-corrosion epoxy composite coating are different, as shown in Table 1.

[0034] Table 1 Addition amount of each component of the anti-corrosion epoxy composite coating in Examples 1-3 / kg Example 1 Example 2 Example 3 Epoxy resin 50 40 60 Alkoxysilane 15 20 10 Titanium Pigments 5 4 6 Additives 2.5 4 1 Solvents 4 2 6 Hexagonal Boron Nitride Preservative 16 18 14 Curing agent 20 10 30 The difference from Example 1 is that the mass ratios of modified hexagonal boron nitride, porous microspheres and polythiophene are different, as shown in Table 2.

[0035] Table 2 Mass ratio of each component of hexagonal boron nitride preservative in Example 1 and Examples 4-5 Example 1 Example 4 Example 5 Modified hexagonal boron nitride 9 10 8 Porous microspheres 1 1 1 Polythiophene 3.5 3 4 The difference from Example 1 is that the modified hexagonal boron nitride is replaced by hexagonal boron nitride.

[0036] The difference from Example 6 is that no porous microspheres are added.

[0037] Comparative Example Comparative Example 1 The difference from Example 1 is that the hexagonal boron nitride type preservative is replaced with the same added amount of hexagonal boron nitride.

[0038] Performance testing Detection Methods Corrosion resistance test Three samples were taken out from Examples 1-7 and Comparative Example 1 respectively, and then coated on steel plates with a specification of 5cm×5cm and a coating thickness of 1mm. After the samples were cured, they were immersed in a 100°C 10wt% NaCl aqueous solution, and the time required for the samples to show abnormalities such as bubbling and degassing was observed. The time was recorded as the corrosion time and the average value was taken. The average value was approximated.

[0039] The test data are shown in Table 3.

[0040] Table 3 Anticorrosion performance of Examples 1-7 and Comparative Example 1 / d Corrosion time / d Corrosion time / d Example 1 166d Example 5 162d Example 2 160d Example 6 154d Example 3 158d Example 7 140d Example 4 164d Comparative Example 1 131d Referring to Examples 1-3 and in combination with Table 3, it can be seen that, relative to Example 1, the corrosion time of Examples 2-3 is relatively shorter, which indicates that when the components of the anti-corrosion epoxy composite coating are added in the amounts of Example 1, the anti-corrosion epoxy composite coating will have better anti-corrosion performance.

[0041] Referring to Example 1 and Examples 4-5 and in combination with Table 3, it can be seen that relative to Example 1, the corrosion time of Examples 4-5 is relatively reduced, which shows that when the modified hexagonal boron nitride, porous microspheres and polythiophene adopt the mass ratio of Example 1, the prepared hexagonal boron nitride type preservative has a better anti-corrosion performance improvement effect on the anti-corrosion epoxy composite coating.

[0042] Referring to Example 7 and Comparative Example 1 and in combination with Table 3, it can be seen that the corrosion time of Example 7 is significantly increased compared with Comparative Example 1, which indicates that the addition of polythiophene can effectively improve the anti-corrosion performance of the hexagonal boron nitride type preservative on the anti-corrosion epoxy composite coating.

[0043] The reason may be that polythiophene is a corrosion inhibitor that can slow down or even prevent metal corrosion. Its anti-corrosion mechanism includes electrochemical protection, passivation and oxygen absorption reaction. Among them, electrochemical protection means that when the corrosive medium contacts polythiophene, polythiophene can prevent the flow of current, thereby reducing the electrochemical corrosion rate of the metal. Passivation means that polythiophene can form an alloy layer with the metal surface, and the alloy layer can change the chemical state of the metal surface to form a passivation film, thereby improving the corrosion resistance of the metal. Oxygen absorption reaction means that polythiophene can participate in the adsorption and release process of oxygen, and affect the kinetics of the corrosion reaction by adjusting the concentration of oxygen on the metal surface.

[0044] Therefore, when polythiophene and hexagonal boron nitride are used at the same time, polythiophene and hexagonal boron nitride will simultaneously provide corrosion protection in multiple aspects such as physical barrier, electrochemical protection, passivation and oxygen absorption reaction, thereby further improving the anti-corrosion performance of hexagonal boron nitride epoxy coating.

[0045] Referring to Examples 6-7 and in combination with Table 3, it can be seen that the corrosion time of Example 6 is significantly increased compared to Example 7, which indicates that the addition of porous microspheres can significantly improve the anti-corrosion performance of the hexagonal boron nitride type preservative on the anti-corrosion epoxy composite coating.

[0046] The reason may be that although polythiophene can exert a synergistic anti-corrosion effect with hexagonal boron nitride, similar to hexagonal boron nitride, polythiophene has relatively poor compatibility with the epoxy coating matrix, that is, polythiophene is difficult to disperse in the epoxy coating, which makes it easy for polythiophene to accumulate or even flow away, resulting in poor anti-corrosion performance of the epoxy coating.

[0047] When porous microspheres, polythiophene and hexagonal boron nitride are used together, polythiophene and hexagonal boron nitride can be loaded in the porous microspheres, and the porous microspheres have excellent compatibility with the epoxy coating. The porous microspheres can also effectively prevent polythiophene and hexagonal boron nitride from direct contact with the epoxy matrix. Then, the polythiophene and hexagonal boron nitride are slowly released through the characteristics of the porous microspheres themselves, thereby significantly improving the anti-corrosion performance of the hexagonal boron nitride epoxy coating.

[0048] Referring to Example 1 and Example 6 and combining with Table 3, it can be seen that the corrosion time of Example 1 is further improved compared with Example 6. This shows that, compared with hexagonal boron nitride, the use of modified hexagonal boron nitride can promote the hexagonal boron nitride type preservative to promote the anti-corrosion epoxy composite coating to have better anti-corrosion performance.

[0049] The reason may be that although porous microspheres can load polythiophene and hexagonal boron nitride, compared with liquid polythiophene, the two-dimensional sheet shape of hexagonal boron nitride itself is more difficult to load on porous microspheres.

[0050] Functionalizing hexagonal boron nitride with nanoparticles can effectively increase the dispersibility of hexagonal boron nitride and maintain its structural integrity, reducing the surface defects of hexagonal boron nitride. Dopamine can effectively improve interfacial adhesion, forming a polydopamine layer on the substrate surface, and can also be compounded with trivalent iron ions or divalent iron ions through catechol to load nano-ferroferric oxide on hexagonal boron nitride, thereby effectively improving the dispersibility of hexagonal boron nitride in epoxy coatings and indirectly improving the anti-corrosion performance of hexagonal boron nitride epoxy coatings.

[0051] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An anti-corrosion epoxy composite coating, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of epoxy resin, 10-20 parts of alkoxysilane, 4-6 parts of pigment, 1-4 parts of auxiliary agent, 2-6 parts of solvent, 14-18 parts of hexagonal boron nitride preservative and 10-30 parts of curing agent, wherein the hexagonal boron nitride preservative contains hexagonal boron nitride and polythiophene.

2. The anti-corrosion epoxy composite coating according to claim 1, characterized in that: The hexagonal boron nitride type preservative consists of modified hexagonal boron nitride, porous microspheres and polythiophene.

3. The anti-corrosion epoxy composite coating according to claim 2, characterized in that: The mass ratio of the modified hexagonal boron nitride, porous microspheres and polythiophene is (8-10):1:(3-4).

4. The anti-corrosion epoxy composite coating according to claim 2, characterized in that: The modified hexagonal boron nitride is dopamine-modified hexagonal boron nitride-nano ferrosoferric oxide.

5. The anti-corrosion epoxy composite coating according to claim 4, characterized in that: The modified hexagonal boron nitride comprises the following raw materials in parts by mass: 200-300 parts of Tris-HCl buffer, 0.5-1.0 parts of dopamine hydrochloride, 1-3 parts of hexagonal boron nitride, 2-5 parts of gamma-aminopropyltriethoxysilane, 0.1-0.3 parts of nano-ferrosoferric oxide and 100-160 parts of N,N-dimethylformamide.

6. The anti-corrosion epoxy composite coating according to claim 5, characterized in that: The preparation method of the modified hexagonal boron nitride comprises the following steps:

1. Preparation of polydopamine modified hexagonal boron nitride First, dopamine hydrochloride is slowly added into Tris-HCl buffer and stirred continuously, then hexagonal boron nitride is quickly added and ultrasonically treated for 2-4 hours, and then balanced at 50-70°C for 12-36 hours, centrifuged and filtered to wash until the filtrate is colorless, and finally solid-liquid separation is performed, and the solid product is vacuum dried to obtain polydopamine-modified hexagonal boron nitride; 2. Preparation of modified nano-iron tetroxide Add nano-ferroferric oxide and γ-aminopropyltriethoxysilane to anhydrous ethanol 20 times the mass of the raw material, then continue stirring for 20-40 minutes, ultrasonic treatment for 3-4 hours, then quickly add deionized water 2 times the mass of the raw material, stir at 70-90°C for 3-5 hours, centrifuge and wash, and vacuum dry to obtain the modified Nano-iron tetroxide; 3. Preparation of modified hexagonal boron nitride The polydopamine-modified hexagonal boron nitride is mixed with N,N-dimethylformamide and ultrasonically treated for 1-2 hours. After forming a suspension, modified ferrosoferric oxide is added, and ultrasonic treatment is performed for 1-2 hours. Thereafter, the mixture is stirred at 100-110° C. for 5-7 hours, and finally, the mixture is centrifugally filtered, washed, and vacuum dried to obtain the modified hexagonal boron nitride.

7. The anti-corrosion epoxy composite coating according to claim 2, characterized in that: The porous microspheres are prepared by mixing trimethylolpropane triacrylate and toluene in a mass ratio of 1:(1-3), then adding 1wt% of the total mass of 2-hydroxy-2-methyl-1-phenyl-1-propanone, and preparing an oil phase under ultrasonic action; The oil phase is mixed with a 1wt% polyvinyl alcohol aqueous solution in a mass ratio of 1:(4-6), and then dispersed and emulsified. The emulsion is then subjected to UV curing treatment. The UV curing treatment conditions are: wavelength 365nm, power 120W, light source 25cm away from the emulsion, irradiation 5min, UV light initiates the self-polymerization of the monomer trimethylolpropane triacrylate to form microspheres, which are then washed and dried to obtain porous microspheres.

8. The anti-corrosion epoxy composite coating according to claim 2, characterized in that: The preparation method of the hexagonal boron nitride preservative is: First, the modified hexagonal boron nitride, polythiophene and ethanol are mixed to obtain a load solution, and then the porous microspheres are added to a three-necked flask equipped with a separatory funnel and a vacuum valve, the load solution is added to the separatory funnel, and then the air in the three-necked flask is removed through the vacuum valve, and the load solution is transferred to the three-necked flask through the separatory funnel, mixed and stirred for 4-6 hours under a vacuum environment, and finally filtered, washed and dried to obtain a hexagonal boron nitride preservative.

9. A method for preparing the anti-corrosion epoxy composite coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. First, epoxy resin and alkoxysilane are mixed, and then continuously stirred at 60-80° C. to obtain an epoxy matrix; S2, adding pigment, additive, solvent and hexagonal boron nitride preservative to the epoxy matrix in sequence, and then mixing and stirring for 10-20 minutes to obtain component A; S3. Mix the curing agent as component B with component A, and then apply the coating to obtain the anti-corrosion epoxy composite coating.

Citation Information

Cited By

  • Non-carbon epoxy static conductive anticorrosive paint and preparation method thereof

    CN120623881A

  • Non-carbon epoxy electrostatic conductive anticorrosive coating and preparation method thereof

    CN120623881B

  • Functionalized boron nitride epoxy composite anti-corrosion coating for load coupling corrosion environment as well as preparation method and application of functional boron nitride epoxy composite anti-corrosion coating

    CN120758115A